Approach, avoidance, and affect: a meta-analysis of approach-avoidance tendencies in manual reaction time tasks - Phaf, R. Hans; Mohr, Sören E.; Rotteveel, Mark; Wicherts, Jelte M. (Frontiers in Psychology, 2014)
Approach action tendencies towards positive stimuli and avoidance tendencies from negative stimuli are widely seen to foster survival. Many studies have shown that approach and avoidance arm movements are facilitated by positive and negative affect, respectively. There is considerable debate whether positively and negatively valenced stimuli prime approach and avoidance movements directly (i.e., immediate, unintentional, implicit, automatic, and stimulus-based), or indirectly (i.e., after conscious or nonconscious interpretation of the situation). The direction and size of these effects were often found to depend on the instructions referring to the stimulus object or the self, and on explicit vs. implicit stimulus evaluation. We present a meta-analysis of 29 studies included for their use of strongly positive and negative stimuli, with 81 effect sizes derived solely from the means and standard deviations (combined N = 1538), to examine the automaticity of the link between affective information processing and approach and avoidance, and to test whether it depends on instruction, type of approach-avoidance task, and stimulus type. Results show a significant small to medium-sized effect after correction for publication bias. The strongest arguments for an indirect link between affect and approach-avoidance were the absence of evidence for an effect with implicit evaluation, and the opposite directions of the effect with self and object-related interpretations. The link appears to be influenced by conscious or nonconscious intentions to deal with affective stimuli.